The Influence Of Healthcare Service Quality On Patient Satisfaction And Revisit Interest At General Hospital Royal Prima Medan - Siahaan, Destri Safhira; Ginting, Chrismis Novalinda; Silaen, Mangatas (UNIVERSITAS PAKUAN, 2017)
The rapid growth of hospitals must be accompanied by a commitment to providing high-quality, professional, and accessible healthcare services. The increasing demands of the community for hospitals to ensure patient satisfaction necessitate continuous improvements in quality management. This study aims to analyze the influence of healthcare service quality on patient satisfaction and revisit intention at Royal Prima Medan Hospital. This research employs a mixed-methods approach with a cross-sectional design. The study population consists of BPJS and non-BPJS patients who received treatment at RSU Royal Prima Medan within the last three months, totaling 18,998 patients. The sample size was determined using Slovin's formula, resulting in 99 respondents. Quantitative data analysis was conducted using univariate, bivariate, and multivariate analyses, while qualitative data analysis involved data reduction, data presentation, and conclusion drawing. The findings indicate that all service quality indicators significantly influence both patient satisfaction and revisit intention, with a significance value of p < 0.05. These results align with qualitative research findings, where interviewees stated that the quality of healthcare services in hospitals plays a crucial role in patient satisfaction and their willingness to return for future services.